The Influence of Service Quality and Perception of Service Price on Patient Satisfaction in The Inpatition Room of Hermina Hospital Palembang - Nabila Pratiwy Mardhiah; Marlina Widiyanti; Muchsin Saggaff Shihab; Mohamad Adam (Syntax Corporation Indonesia, 2023)
This research was conducted with the aim of determining the influence of service quality and perceived service prices on patient satisfaction in the inpatient room at Hermina Hospital, Palembang. The population in this study were inpatients at the Hermina Palembang Hospital for the period March 2022 to March 2023, totaling 10,670 patients. Based on sample calculations, the sample that will be used in this research is 122 respondents who are inpatients at Hermina Palembang Hospital who were treated without payment using National Health Insurance in the period March 2022 to March 2023 who were informed by telephone, WhatsApp or direct visit. by distributing questionnaires via Google Form using purposive sampling techniques. The results of multiple linear analysis show that service quality and perceived service price have a positive and significant effect on patient satisfaction. It is hoped that the results of this research will enable Hermina Palembang Hospital to evaluate the barriers to not being able to provide patient payment services more quickly regarding service quality. Price perception, it is hoped that an evaluation can be carried out based on the price offered. Management needs to do research in determining prices with existing hospital competitors, especially in the Palembang area.